2021
DOI: 10.2478/mmcks-2021-0013
|View full text |Cite
|
Sign up to set email alerts
|

Marketing communication tools and their influence on marketing innovation: Evidence from Slovakian SMEs

Abstract: Due to lack of sources, SMEs face certain problems when applying innovative activities. Since marketing communication tools enable to perform innovative actions, SMEs’ usage of such channels might provide solutions for them to overcome the barriers of making innovation. Thus, this paper investigates whether the usage of marketing communication tools by SMEs enables them to be innovative in marketing or not, and the research question is “Does the usage of marketing communication tools by SMEs improve their inno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…This study proposes that marketing communication system has positive role to promote management innovation. According to the earlier studies, marketing communication system has positive effect on innovation activities of the company (Civelek, Červinka, Gajdka, & Nétek, 2021). Better system of marketing communication in the organization can lead to the better management innovation.…”
Section: Integrated Marketing Communicationmentioning
confidence: 96%
“…This study proposes that marketing communication system has positive role to promote management innovation. According to the earlier studies, marketing communication system has positive effect on innovation activities of the company (Civelek, Červinka, Gajdka, & Nétek, 2021). Better system of marketing communication in the organization can lead to the better management innovation.…”
Section: Integrated Marketing Communicationmentioning
confidence: 96%
“…Innovation includes organizational capacity to introduce and implement new ideas, some products, processes, and knowledge within the organization (Civelek, Červinka, Gajdka, & Nétek, 2021) which are considered as aspects of culture (Roach, Ryman, & White, 2014), and resources to introduce and implement new ideas, some products, processes, and knowledge within the organization (Wahyuni, 2021). Organizational ability to transform knowledge and ideas into processes, new products, and systems into management strategies for the benefit of the company and stakeholders reflects innovation capability (Silva, 2014).…”
Section: Literature Review and Hypothesis Development 21 Innovationmentioning
confidence: 99%
“…As two of the IMC components, the response to market changes and message integration positively impact performance [30]. Research has also shown that using marketing communication tools improves SMEs' innovativeness in marketing [31]. For a more direct approach to connecting with sustainability, IMC can help convey information about sustainable products, encourage thoughtful buying decisions, and raise awareness about the consequences of excessive consumption and waste.…”
Section: Literature Reviewmentioning
confidence: 99%